Analisis Tentang Konsep Holding Ultra Mikro BUMN Ditinjau Dari Aspek Hukum Persaingan Usaha - Muhammad Sabil Bakti (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The economic development of a country is inseparable from the role of the government that takes part in this development. In carrying out the mandate of Article 33 of the 1945 Constitution, the state is not directly involved in managing businesses that concern the livelihood of many people, but this is done through BUMN. In order to face challenges from within and outside the country so as to be able to compete in the business world, and as a sustainable arrangement as well as improving the performance and value of BUMN, the Ministry of BUMN formed BUMN holding in certain sectors. One form of holding carried out in the ultra-micro sector is the ultra-micro holding (UMi) by BRI, PT Pegadaian, and PT PNM, the process of forming the UMi holding is very interesting to study. The type of research used is normative juridical type, primary legal material in the form of legislation, secondary legal material in the form of books, legal writings or journals. Based on the formulation of problems related to the formation of the UMi holding, whether the formation of the UMi holding is in accordance with positive provisions in Indonesia and does not lead to violations of business competition law, this study concludes that the formation of the UMi holding is in line and in accordance with the applicable statutory provisions in Indonesia and the holding does not lead to the occurrence of monopolistic acts and unfair business competition or business competition law.